MORPHOLOGICAL DESCRIPTION OF SECTIONS AND SELECTION OF SOIL SAMPLES IN ZHAMBYL REGION (Eurasian Journal of Ecology, 2024)
Soil contamination with heavy metals, especially in the vicinity of large cities and industrial centers, has become one of the pressing environmental problems. Over the past ten years, the Republic of Kazakhstan has seen a moderate increase in industrial output, with coal production growing by 20%, crude oil and natural gas production by 19%, and metal ore production by 27%. Technogenic pollutants enter the soil in the form of complex organic and mineral compounds, as well as in a metallic state, with subsequent decomposition to simple elements or the formation of new compounds. All this directly affects the environment, deteriorating soil-ecological conditions, and reducing soil fertility. In this regard, we carried out an analysis of the ecology of the soil cover, assessed the condition of the soil and the problems of their solution in the Zhambyl region. Analysis of the study showed that the negative impact of emissions from industrial enterprises and the growing amount of emissions from mobile sources on soil and plants has a strong impact on the soil surface, devoid of vegetation and susceptible to erosion processes. The obtained research results will make it possible to satisfy the need for fertilizers through the use of local raw materials, ensuring the preservation of soil fertility, increasing crop productivity, and obtaining environmentally friendly products at significantly lower costs. The article shows the results of comparison with the surface of damaged and cut off points P-1, P-2, P-3, P-4. Violations of the soil-ecological function of technogenic landscapes destroyed by emissions from mining and metallurgical enterprises were identified.Key words: heavy metals, soil, production, erosion, pollution.